Habitat Suitability for Endemic and Vulnerable White-Naped Tit (Machlolophus nuchalis) in Arid and Semi-Arid Landscapes of India - Choudhary Rounak; Sharma Vivek; Dutta Subroto; Mathur Praveen; Singh Pawan; Sahu Harish (Journal of Landscape Ecology)
The White-naped Tit (Machlolophus nuchalis) is a vulnerable bird endemic to India that faces serious threats due to habitat loss, degradation, and fragmentation of habitat. Using MaxEnt niche modelling and compiled species occurrence data, we predicted White-naped Tit's habitat suitability in India's arid and semi-arid biogeographic zones. Our analysis suggests that 6.74 % (~50,612 km²) of the total area is suitable for White-naped Tit. Land cover change detection reveals that rangelands that contain suitable habitat types, support the preferred flora of Acacia spp. and have the high frequency of sightings for the target species, are the most declining form of land cover in the study area. Our findings help to provide a baseline understanding of the White-naped Tit's range and its association with land cover and other physical factors, which may be taken in consideration for short- and long-term conservation management approaches for this threatened species